Compact ultra-wideband monopole antenna loaded with metamaterial - Al-Bawri, Samir Salem; Goh, Hui Hwang; Islam, Md Shabiul; Wong, Hin Yong; Jamlos, M. F.; Narbudowicz, Adam; Muzammil, Jusoh; Thennarasan, Sabapathy; Rizwan, Khan; Islam, Mohammad Tariqul (MDPI, 2020)
A printed compact monopole antenna based on a single negative (SNG) metamaterial is proposed for ultra-wideband (UWB) applications. A low-profile, key-shaped structure forms the radiating monopole and is loaded with metamaterial unit cells with negative permittivity and more than 1.5 GHz bandwidth of near-zero refractive index (NZRI) property. The antenna offers a wide bandwidth from 3.08 to 14.1 GHz and an average gain of 4.54 dBi, with a peak gain of 6.12 dBi; this is in contrast to the poor performance when metamaterial is not used. Moreover, the maximum obtained radiation efficiency is 97%. A reasonable agreement between simulation and experiments is realized, demonstrating that the proposed antenna can operate over a wide bandwidth with symmetric split-ring resonator (SSRR) metamaterial structures and compact size of 14.5 × 22 mm2 (0.148 λ0 × 0.226 λ0) with respect to the lowest operating frequency.